Vestibular function after simultaneous bilateral cochlear implantation in adults - Yokoi, Jun; Fujita, Takeshi; Uehara, Natsumi; Iwaki, Shinobu; Kakigi, Akinobu; Nibu, Ken-ichi (Frontiers in Neurology, 2023)
Introduction: Binaural hearing enhances speech intelligibility, source localization, and speech comprehension in noisy environments. Although bilateral cochlear implantation (CI) offers several benefits, concerns arise regarding the risk of bilateral postoperative vestibular dysfunction with simultaneous CI. This study aimed to longitudinally evaluate changes in vestibular function in adult patients who underwent simultaneous bilateral CI using minimally invasive electrodes and surgical techniques.A retrospective review was conducted on 10 patients who underwent simultaneous bilateral CI at our hospital. Vertigo symptoms and vestibular function test results were examined preoperatively, 1-6 months postoperatively, and 1 year postoperatively. Nystagmus tests, caloric reflex tests, vestibular evoked myogenic potentials (VEMP) measurements, and static stabilometry were performed as vestibular function tests.Although an initial transient decline in vestibular function was observed, no significant long-term decline was observed in the caloric reflex test, ocular VEMP (oVEMP), or cervical VEMP (cVEMP). Moreover, regardless of the presence or absence of abnormalities in caloric reflex, This is a provisional file, not the final typeset article oVEMP, or cVEMP, no significant deterioration was detected in the static stabilometer test. While two patients reported preoperative dizziness, all patients were symptom-free one year postoperatively.The findings suggest that using current minimally invasive electrodes and surgical techniques in simultaneous bilateral CI leads to temporary vestibular function decline postoperatively. However, most patients experience a recovery in function over time, highlighting the potential safety and efficacy of the procedure. Simultaneous bilateral CI surgery is viable, depending on the patient's auditory needs and burden.